Pemberian Hak Administrasi Kependudukan Bagi Pasangan Kawin Belum Tercatat Perspektif Tujuan Hukum Gustav Radbruch - Mahasina, Mohammad Wildan Raja; Isroqunnajah, Isroqunnajah; Hidayah, Khoirul (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This study's purpose is to see the application of policies to accommodate population administration rights for unregistered married couples at the Population and Civil Registration Office of the Gresik Regency. This research is field research presented with a qualitative descriptive approach based on Gustav Radbruch's theory of legal objectives. Data is obtained by going directly to the field by conducting interviews with relevant department employees and documentation. The results of this study indicate that the provision of population administration rights for unregistered married couples at the Population and Civil Registration Office of Gresik Regency is following policy procedures and does not violate the rules. Based on Gustav Radbruch's idea of legal philosophy about the purpose of law, the granting of population administration rights for unregistered married couples has fulfilled the elements of legal objectives, namely justice, legal certainty, and legal benefits. Legal justice is indicated by the fulfillment of the constitutional rights of unregistered married couples to obtain public services equally. Married couples who do not have a marriage certificate or marriage certificate can still record their marriage as husband and wife on the family card. Legal certainty is indicated by the fulfillment of procedures by applicable regulations. Legal expediency is indicated by the fulfillment of the civil rights of children of unregistered married couples in the form of ownership of birth certificates containing the names of the father and mother parents.